Contribution of hypoxia-inducible factor 1alpha to pathogenesis of sarcomeric hypertrophic cardiomyopathy - Raj Murthi, S; Petry, A; Shashikadze, B; Stöckl, JB; Schmid, M; Santamaria, G; Klingel, K; Kračun, D; Chen, X; Bauer, S; Schmitt, JP; Flenkenthaler, F; et al. (Nature Research, 2025)
Hypertrophic cardiomyopathy (HCM) caused by autosomal-dominant mutations in genes coding for structural sarcomeric proteins, is the most common inherited heart disease. HCM is associated with myocardial hypertrophy, fibrosis and ventricular dysfunction. Hypoxia-inducible transcription factor-1α (Hif-1α) is the central master regulators of cellular hypoxia response and associated with HCM. Yet its exact role remains to be elucidated. Therefore, the effect of a cardiomyocyte-specific Hif-1a knockout (cHif1aKO) was studied in an established α-MHC719/+ HCM mouse model that exhibits the classical features of human HCM. The results show that Hif-1α protein and HIF targets were upregulated in left ventricular tissue of α-MHC719/+ mice. Cardiomyocyte-specific abolishment of Hif-1a blunted the disease phenotype, as evidenced by decreased left ventricular wall thickness, reduced myocardial fibrosis, disordered SRX/DRX state and ROS production. cHif1aKO induced normalization of pro-hypertrophic and pro-fibrotic left ventricular remodeling signaling evidenced on whole transcriptome and proteomics analysis in α-MHC719/+ mice. Proteomics of serum samples from patients with early onset HCM revealed significant modulation of HIF. These results demonstrate that HIF signaling is involved in mouse and human HCM pathogenesis. Cardiomyocyte-specific knockout of Hif-1a attenuates disease phenotype in the mouse model. Targeting Hif-1α might serve as a therapeutic option to mitigate HCM disease progression.